What Do Women Want? A Qualitative Study of Dating. (February 2016) - Noel, Nora E.; Ogle, Richard L.; Maisto, Stephen A.; Jackson, Lee A.
Many approaches to decrease unwanted sex for women emphasize enhanced risk recognition. However, women often remain in risky situations despite recognition; so we need to understand the attractions of normative dating and sex. In this focus group study, 45 young adult women discussed their attractions to men, dating, and sex. Themes emerged describing conflicts between what they wanted, dating realities, desire for "traditional" behavior from the man, alcohol use, sexual arousal (hers and his), indirect communication about sex, feeling "obligated, " and enhanced self-esteem. Results suggest improving risk-recognition programs by examining and clarifying women's goals for dating and putting positive emphasis on "have fun, achieve your goals, but try to avoid harm in the process."